THE RELATIONSHIP BETWEEN ECONOMIC DEVELOPMENT AND DEFORESTATION RATE IN INDONESIA - , Efendi Agus Waluyo, S.Hut. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Tropical deforestation is one of the most serious environmental problems discussed on a global scale in recent times.Indonesia has suffered from a deforestation problem for the last few decades while the country experiencedthe economic growth acceleration by extracting natural resources.Analyzing the relationship between deforestation and economic development within Indonesia will provide valuable information for the government to determine trade-off between them.The mainobjective of this study is to economically and statistically demonstrate the relationship between the economic development and thedeforestationrate in Indonesia and find out the turning point at which the increase in income level does not lead to the increase in deforestation rate. For this purpose, this study uses time series data over 46 years from 1962 to 2007 and applies the autoregressive distributed lag (ARDL) bounds testing approach for cointegration developed by Pesaran and Shin (1998) recently to examine the EKC hypothesis. The main reason for this is because therehas been no study on EKC for deforestation in Indonesia investigated by using time series so far. The dependent variable is deforestation rate and independent variables are real GDP per capita (GDP), population growth (POPGRW), rural population (RPOPDEN), agricultural index (AGI), agricultural land (AGL),roundwood production (RWOOD), and forest product export (FOREXP). The results show that both the linear and non-linear terms of GDP per capita confirm the existence of the inverted-U relationship between economic growth and deforestation rate in the long-run.The results suggest that the deforestation rate increases at the initial stage of economic growth and declines after a threshold point.The income turning point (ITP) of the EKC in this researchwas calculated to beUS $ 990.4.The analysis of short-run dynamics also indicates that the coefficients of GDP and GDP 2 are reasonable in terms of EKC, and the deviation from the long-run equilibrium is quickly adjusted. Moreover, we obtained the findings that rural population (RPOP), agricultural index (AGI), and roundwood (RWOOD) productionhave a negative and significant effect on the deforestation. The long-run model passed all the diagnostic tests successfully (LM test, normality test of residual term, White heteroscedasticity), and it was confirmed that all the parameters estimated in the model are stable from the plots of CUSUM and CUSUMSQ. In order to reduce the deforestation rate, the Indonesian government should focus on improving technology in agriculture. Technological progress in agriculture must reduce the pressure on land demand and slow the deforestation.Â